Aquisição de alimentos orgânicos pelo Programa Nacional de Alimentação Escolar no Paraná - Ana Beatriz Goes Maia Marques; Rozane Marcia Triches (Desenvolvimento e Meio Ambiente, 2022)
The present work aims to identify the main obstacles faced and the ways to overcome the acquisition and supply of organic food from family farming by the actors involved in the PNAE in municipalities in the state of Paraná, in addition to pointing out the positions of the actors involved on the organic food from family farming. For this study, 11 municipalities were selected based on the acquisition and non-acquisition of organic food from family farming, the size of the population, and the state's macro-regions. In total, 50 interviews were conducted with three distinct segments: farmers' organizations responsible for the food supply, municipal managers, and school principals and cooks. As a result, the main limitations were: quantity, logistics, certification, organic food cost, registration with MAPA, and lack of agroecological ATER. Regarding overcoming the problems, it was emphasized the mandatory purchase of these foods, enacted in law in the municipality, greater incentive, the organization of family farming around agroecological production, articulation, and dialogue between the actors involved, and greater mastery over the theme. Although, in general, the participating actors highlight positive aspects of organic food from family farming, it was found that there is a lack of knowledge about agroecological production and public policies that favor the acquisition and supply of organic food. The study also highlighted that public policy alone was not enough to take effect in each municipality, requiring the actors involved to be proactive.